HUKUM INVESTASI BODONG KATERING YANG DILAKUKAN OLEH IBU RUMAH TANGGA DI KEBUMEN - Pingky Fordora; Gunardi Lie; Moody R. Syailendra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
A fraudulent investment made by a housewife with the initials SP in Kebumen under the guise of a catering business. At present, many people only know the word investment, but do not fully understand what investment is and the consequences of investing. The purpose of writing scientific papers on investment law is as follows: knowing the meaning of fraudulent investments that occur in social life, knowing several factors that make someone make fraudulent investments in public life, knowing what law will be imposed on someone who invests fraudulent, and find out what is the best solution so that people no longer make fraudulent investments. The method I use in writing this scientific paper is a qualitative method. Mrs. SP started her action by deceiving residents of Cilincing District, North Jakarta City under the guise of opening a catering business and for people or residents who want to invest in her business, they will be given a profit of 10 percent every month. From this case, we can see that fraudulent investment is not just a joke, but fraudulent investment can harm many parties. If you make fraudulent investments, other than that, making fraudulent investments will not make you rich in the long term, because sooner or later the perpetrators will be caught by both the police and the people who report them.